2019
DOI: 10.1021/acsphotonics.9b01435
|View full text |Cite
|
Sign up to set email alerts
|

Subliming GaN into Ordered Nanowire Arrays for Ultraviolet and Visible Nanophotonics

Abstract: We report on the fabrication of ordered arrays of InGaN/GaN nanowire quantum disks by a top-down selective-area sublimation method. Using a combination of two-dimensional molecular beam epitaxy of InGaN/GaN quantum wells, electron-beam lithography and ultrahigh-vacuum sublimation techniques, we demonstrate that the position, geometry and dimensions of nanowires can be finely controlled at nano-, micro-and macro-scales. Relying on structural data, we evaluate in particular the relative sublimation rates of GaN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…The latter method does not necessitate any post-processing cleaning and even allows for epitaxial regrowth straight after NW formation [18,20]. Most importantly, in the frame of the GaN sublimation method, we have shown that it is possible to achieve a fine control of the NW position, dimensions 2 and geometry on nano, micro and macro scales [8]. As a result, this method has led to the realization of various photonic elements operating at room-temperature such as metalenses [21], NW-induced photonic crystal nanocavities [8] and photonic nanolasers based on Fabry-Pérot resonances [7,8].…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…The latter method does not necessitate any post-processing cleaning and even allows for epitaxial regrowth straight after NW formation [18,20]. Most importantly, in the frame of the GaN sublimation method, we have shown that it is possible to achieve a fine control of the NW position, dimensions 2 and geometry on nano, micro and macro scales [8]. As a result, this method has led to the realization of various photonic elements operating at room-temperature such as metalenses [21], NW-induced photonic crystal nanocavities [8] and photonic nanolasers based on Fabry-Pérot resonances [7,8].…”
mentioning
confidence: 91%
“…Building on the strengths of this semiconductor compound family, the research community has recently focused on GaN nanowires (NWs) to realize even more advanced optoelectronic and photonic devices with new functionalities, higher efficiency, smaller footprint or lower energy cost: e.g. flexible light-emitting diodes [1], single photon sources [2,3] or even photon [4][5][6][7][8], plasmon [9][10][11] and polariton nanolasers [12]. Most GaN nanowires are now realized in the frame of bottom-up epitaxial processes based either on molecular beam epitaxy [13][14][15] or on metal-organic chemical vapor deposition [15][16][17].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Because nanowires typically have wavelength-scale diameters they act as waveguides; the end-facet cavity reflectivity in a nanowire laser is a complex function of the facet structure, nanowire diameter, the transverse lasing mode, and the refractive index of the medium. 24 As such, it is common for a given growth of nanowire lasers to have a large wire-to-wire variation in emission 25 or lasing performance. 26 This spread can mask optimizations in underlying material properties or gain, which might otherwise be clearly observed.…”
Section: Introductionmentioning
confidence: 99%